ASSUÉFRY: NOUVEAU PÔLE DE TRANSACTIONS TRANSFRONTALIÈRES DU NORD-EST DE LA CÔTE D’IVOIRE - Téré, Gogbe; Diabagate, Abou; Homiengnon, Yeo; Kossonou, Koffi (European Scientific Journal, ESJ, 2014)
The cross-border space of Assuéfry is a crossroads of exchanges between populations of the same zone, with the rest of the country but also with the countries of the sub-region West African. This cross-border position of Assuéfry in the northeast of Ivory Coast, far from being an obstacle to the human setting-up, constitutes on the contrary a zone convenient to the blooming and to the activities of the man. Indeed, considered as one of the localities the most populated with the region of Gontougo with 22699 inhabitants, the sub-prefecture of Assuéfry, in consideration of its border position, presents an ideal frame for the development of economic activities generally and trade in particular. But unfortunately this space has hardly a center deserving of exchanges commercial which can impulse a real development of the activities. It is only the market, the weekly market which holds place of frame of exchanges the speciality of which is the trade especially of the food-producing.